Different Effects of Vitamin C-Based Supplements on the Advance of Linseed Oil Component Oxidation and Lipolysis during In Vitro Gastrointestinal Digestion - Bárbara Nieva-Echevarría; Encarnación Goicoechea; Patricia Sopelana; María D. Guillén (Foods, 2021)
Although widely consumed, dietary supplements based on Vitamin C contain high doses of this compound, whose impact on lipid oxidation during digestion needs to be addressed. Therefore, the effect of seven commercial supplements and of pure l-ascorbic acid and ascorbyl palmitate on linseed oil during in vitro gastrointestinal digestion was tackled. The advance of lipid oxidation was studied through the generation of oxidation compounds, the degradation of polyunsaturated fatty acyl chains and of gamma-tocopherol, by employing Proton Nuclear Magnetic Resonance. Supplements containing exclusively l-ascorbic acid enhanced the advance of linseed oil oxidation during digestion. This was evidenced by increased formation of linolenic-derived conjugated hydroxy-dienes and alkanals and by the generation of conjugated keto-dienes and reactive alpha,beta-unsaturated aldehydes, such as 4,5-epoxy-2-alkenals; moreover, gamma-tocopherol was completely degraded. Conversely, supplements composed of mixtures of ascorbic acid/salt with citric acid and carotenes, and of ascorbyl palmitate, protected linseed oil against oxidation and reduced gamma-tocopherol degradation. The study through Solid Phase Microextraction-Gas Chromatography/Mass Spectrometry of the volatile compounds of the digests corroborated these findings. Furthermore, a decreased lipid bioaccessibility was noticed in the presence of the highest dose of l-ascorbic acid. Both the chemical form of Vitamin C and the presence of other ingredients in dietary supplements have shown to be of great relevance regarding oxidation and hydrolysis reactions occurring during lipid digestion.